2015
DOI: 10.1155/2015/854015
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between CYP3A4 and Dietary Polyphenols

Abstract: The human cytochrome P450 enzymes (P450s) catalyze oxidative reactions of a broad spectrum of substrates and play a critical role in the metabolism of xenobiotics, such as drugs and dietary compounds. CYP3A4 is known to be the main enzyme involved in the metabolism of drugs and most other xenobiotics. Dietary compounds, of which polyphenolics are the most studied, have been shown to interact with CYP3A4 and alter its expression and activity. Traditionally, the liver was considered the prime site of CYP3A-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
124
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 195 publications
(204 reference statements)
0
124
0
1
Order By: Relevance
“…Amongst the CYP enzymes which are responsible for the metabolism of a wide array of endogenous substances, (example-steroids, hormones, lipids, and bile acids), xenobiotics (example-drugs and pollutants from the environment), and dietary products and/dietary polyphenols, CYP 3A4 has been shown to be the major enzyme that is involved in the metabolism of drugs and xenobiotics in the liver and gut (Loai and Zohar, 2015). It has also been shown to be expressed in the prostate, breast, gut, colon, small intestine, and the brain (Ferguson and Tyndale, 2011; Loai and Zohar, 2015).…”
Section: Adverse Effects Associated With Uncontrolled and Long-lastinmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the CYP enzymes which are responsible for the metabolism of a wide array of endogenous substances, (example-steroids, hormones, lipids, and bile acids), xenobiotics (example-drugs and pollutants from the environment), and dietary products and/dietary polyphenols, CYP 3A4 has been shown to be the major enzyme that is involved in the metabolism of drugs and xenobiotics in the liver and gut (Loai and Zohar, 2015). It has also been shown to be expressed in the prostate, breast, gut, colon, small intestine, and the brain (Ferguson and Tyndale, 2011; Loai and Zohar, 2015).…”
Section: Adverse Effects Associated With Uncontrolled and Long-lastinmentioning
confidence: 99%
“…It has also been shown to be expressed in the prostate, breast, gut, colon, small intestine, and the brain (Ferguson and Tyndale, 2011; Loai and Zohar, 2015). …”
Section: Adverse Effects Associated With Uncontrolled and Long-lastinmentioning
confidence: 99%
“…Despite being a potent phytomolecule, the use of Mgf is restricted due to its low and variable oral bioavailability (about 1.5 to 5.0%), usually ascribed to its poor aqueous solubility (0.1 to 0.3 mg/mL), low lipophilicity, high P-gp efflux, considerable first-pass metabolism and cytochrome P-450 mediated metabolism in gut enterocytes (Basheer and Kerem, 2015;Khurana et al, 2016). Besides, Mgf display rapid clearance from the body via glucuronidation of the hydroxyl groups present at position-6 and 7 of its xanthone moiety, which, in turn, tends to reduce its potential antioxidant and anticancer activities, due to shorter half-life (van der Merwe et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CYP3A4 interacts with dietary phenolic compounds. This suggests that coadministration of drugs and phenolic compounds may stimulate some toxicity consequences 38 .…”
Section: Phase I: Metabolism Of Dietary Phenolic Compoundsmentioning
confidence: 99%
“…The metabolic action of CYP450 on phenolic compounds depends largely on their functional groups, molecular weight, stereostructure, glycosylation, polymerization, and conjugation with other phenolic compounds 38,39 . Moreover, flavonoids rich in hydroxylic groups are less likely to be metabolized by CYP450; paradoxically, tea catechins (flavonoids rich in hydroxyl groups) are reported to inhibit CYP450 40 .…”
Section: Phase I: Metabolism Of Dietary Phenolic Compoundsmentioning
confidence: 99%